2009
DOI: 10.1088/0022-3727/42/10/105506
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresistance and giant magnetoresistance of magnetorheological elastomers

Abstract: A new magnetorheological elastomer composite (MRE) was developed with a resistance which is strongly sensitive both to temperature and pressure. The electrical resistance of this MRE was investigated versus pressure and temperature. The resistance of the composite was recorded versus pressure for seven different values of the temperature. The mechanism of electrical conduction was modeled and assessed experimentally. An other type of composite, prepared with a softer elastomer, showed a giant magnetoresistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 13 publications
1
70
1
Order By: Relevance
“…The addition of the conductive doping is the most common method for improving the conductivity of the MR materials [23][24][25]. Li et al developed the high performance MREs with excellent mechanical and electrical properties by using graphite 5 as the additive [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of the conductive doping is the most common method for improving the conductivity of the MR materials [23][24][25]. Li et al developed the high performance MREs with excellent mechanical and electrical properties by using graphite 5 as the additive [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this logical prediction, the coupling between the magnetization status and the resistance in magnetic elastomers was rarely investigated. 14,15 This paper reports a magneto-piezoresistance (MPR) effect in an elastomagnetic composite that gives a resistance decrement of about 60% under a magnetic induction field gradient of 3 T/m. The investigated composites were bar shaped samples made of Ni microparticles (Ni MPs) dispersed into a silicone matrix, in a volume fraction (vol%) of about 40%.…”
Section: Introductionmentioning
confidence: 99%
“…The iron microparticles are connected to the polymer chains of the elastic matrix [3,9,13,23,25]. Then, due to the action of F, the elastic matrix reacts with the elastic force F el .…”
Section: Denotinǧmentioning
confidence: 99%
“…It has been recently shown that MRSs modify their conductivity by compression [22,23], heating [24], under the influence of an external magnetic field [25].…”
Section: Introductionmentioning
confidence: 99%